HUQUQSHUNOSNING NUTQ ODOBI (Conference Zone, 2022)
This article directly discusses the role of speech etiquette in society in relation to the importance of legal practice. It also discusses the key issues that have been done, are being done and should be done to develop speech etiquette in legal relationships.